Dried Noodles Enriched with Black Soldier Fly Larvae Flour as a Novel Strategy for Stunting Prevention - I Gusti Ayu Krisma Widya Saraswati; I Gusti Agung Bulan Mutiara Dewi; Kunti Dewi Dhasi Aryawan; Putu Cempaka Sekarhita; Putu Wedanta Darma Wiguna; Made Dita Dewi Devani; Ida Ayu Tisna Wahyuniari; I Gede Arie Mahendra Putra; I Wayan Ryantama Swastika Braja; Ni Made Defy Januarinti (Warmadewa University Press, 2026)
Stunting remains a major public health problem in Indonesia and is closely associated with chronic protein deficiency in children. The development of affordable, nutrient-dense food products is therefore essential to support stunting prevention programs. This study aimed to develop protein-enriched dried noodles using Black Soldier Fly Larvae (BSFL) flour as an alternative functional food ingredient and to evaluate their sensory and proximate characteristics. Dried noodles were formulated with three different substitution ratios of BSFL flour to wheat flour, namely 50:50, 60:40, and 40:60. Sensory evaluation was conducted using a hedonic test involving 20 semi-trained panelists to assess color, aroma, texture, taste, and overall acceptability. The formulation with the highest sensory acceptance was further subjected to proximate analysis, including protein, moisture, and ash content. The results indicated that the formulation 50:50 achieved the highest overall acceptability score and was categorized as “liked” by panelists. Proximate analysis of the selected formulation showed a protein content of 23.3%, moisture content of 12.9%, and ash content of 5.3%. The moisture content met the Indonesian National Standard (SNI 8217:2015) requirement for dried noodles, indicating good product stability. The incorporation of BSFL flour significantly increased the protein content of dried noodles compared to conventional wheat-based products while maintaining acceptable sensory quality. In addition, the use of insect-based protein supports sustainable food production by utilizing environmentally friendly resources. Overall, BSFL-enriched dried noodles demonstrate strong potential as a high-protein functional food product that can contribute to improving dietary protein intake and supporting stunting reduction efforts in Indonesia.